A flexible two‐surface gradient‐extended damage‐plasticity model for large deformations with nonlinear kinematic hardening. Issue 1 (17th December 2018) - Brepols, Tim; Wulfinghoff, Stephan; Reese, Stefanie
Abstract: A novel 'two‐surface' gradient‐extended damage‐plasticity model for large deformations is discussed which can be considered the geometrically nonlinear version of a corresponding model for small deformations developed recently [1, 2]. The 'two‐surface' approach makes the model flexible in the sense that it can be adapted to various situations in which the considered material's behavior is either (quasi‐)brittle‐like, ductile‐like or possibly something in between. Nonlinear kinematic and isotropic hardening as well as nonlinear damage hardening are accounted for by the model which is finally formulated in terms of symmetric internal variables only, being advantageous not only from the computational point of view. Selected theoretical and numerical aspects are briefly discussed and a numerical example practically illustrates the model's functionality.